Influencia de un modelo de implantación de sistemas de planeación de recursos empresariales en la gestión del conocimiento de una empresa corporativa de Trujillo - Mendoza De Los Santos, Alberto Carlos (2010)
This work aims to propose and analyze an implementation model of enterprise resource planning (ERP) systems, filled with activities of knowledge management, in order to exploit the situation for implementing the benefit of including the elementary principles of the first one into the second one, in favor of the corporate enterprise under study . The interest was focused on finding the synergy between two forces, one from the technology and the other one from the management, to produce in the company, cultural openness regarding the creation, storage, dissemination and use of its intangible most valuable resource named "knowledge." The study takes advantage of the situation of implementing an ERP system in Trujillo Corporation, following the model of the Spanish company IBdos to incorporate in it, aspects of knowledge management methodology proposed by the European Committee for Standardization (CEN) resulting in a hybrid that takes advantage of resources, and grow activities of knowledge management. The result was able to demonstrate a positive change in the organization in relation to the management of knowledge; as evidenced through the variables: cultural change with regard to knowledge management, development of skills in employees to create and manage knowledge, and development of an internal methodology to facilitate knowledge management. Finally, we measured the degree of maturity of the organization with regard to knowledge management before and after the process of the ERP system, implementation, concluding that the improvement in corporate performance is low.